External skeletal robusticity of children and adolescents - European references from birth to adulthood and international comparisons - Mumm, Rebekka; Godina, Elena; Koziel, Slawomir; Musalek, Martin; Sedlak, Petr; Wittwer-Backofen, Ursula; Hesse, Volker; Dasgupta, Parasmani; Henneberg, Maciej; Scheffler, Christiane (Anthropologischer anzeiger, 2018)
ABSTRACT: Background: In our modern world, the way of life in nutritional and activity behaviour has changed. As a consequence, parallel trends of an epidemic of overweight and a decline in external skeletal robusticity are observed in children and adolescents. Aim: We aim to develop reference centiles for external skeletal robusticity of European girls and boys aged 0 to 18 years using the Frame Index as an indicator and identify population specific age-related patterns. Methods: We analysed cross-sectional & longitudinal data on body height and elbow breadth of boys and girls from Europe (0-18 years, n = 41.679), India (7-18 years, n = 3.297) and South Africa (3-18 years, n = 4.346). As an indicator of external skeletal robusticity Frame Index after Frisancho (1990) was used. We developed centiles for boys and girls using the LMS-method and its extension. Results: Boys have greater external skeletal robusticity than girls. Whereas in girls Frame Index decreases continuously during growth, an increase of Frame Index from 12 to 16 years in European boys can be observed. Indian and South African boys are almost similar in Frame Index to European boys. In girls, the pattern is slightly different. Whereas South African girls are similar to European girls, Indian girls show a lesser external skeletal robusticity. Conclusion: Accurate references for external skeletal robusticity are needed to evaluate if skeletal development is adequate per age. They should be used to monitor effects of changes in way of life and physical activity levels in children and adolescents to avoid negative health outcomes like osteoporosis and arthrosis.
Keywords: mladiství; Infant, Newborn; dítě; Infant; Humans; Evropa; Nutritional Status; referenční hodnoty; kojenec; Female; Reference Values; novorozenec; Child, Preschool; Male; tělesná výška; ženské pohlaví; Europe; Child; nutriční stav; Body Mass Index; Cross-Sectional Studies; Body Height; index tělesné hmotnosti; předškolní dítě; Adolescent; průřezové studie; lidé; mužské pohlaví